Aqueous speciation is likely to control the stable isotopic fractionation of cerium at varying pH. (1st December 2017) - Nakada, Ryoichi; Tanaka, Masato; Tanimizu, Masaharu; Takahashi, Yoshio
Abstract: Cerium (Ce) can be used as a plaeoredox proxy as shown by a recent study of stable isotopic fractionation of Ce during adsorption and precipitation. However, the experiments in that study were performed at pH conditions lower than that of natural seawater. In the current study, adsorption and precipitation experiments were performed at pH 6.80, 8.20, and 11.00 with 2.25 mM dissolved carbonate to simulate Ce isotopic fractionation in the natural environment and examine the relationship between isotopic fractionation and Ce speciation in the liquid phase. Mean isotopic fractionation factors between liquid and solid phases (αLq-So ) of Ce adsorbed on ferrihydrite did not depend on pH conditions or dissolved Ce species. In the Ce/δ-MnO2 system, αLq-So values decreased from 1.000411 (±0.000079) to 1.000194 (±0.000067) with increasing pH or number of carbonate ions, from Ce 3+ to Ce(CO3 )2 − . In the Ce/precipitation system at pH 8.20 and 11.00 where Ce(CO3 )2 − is present in solution, the αLq-So values were 0.999821 (±0.000071) and 0.999589 (±0.000074), respectively, meaning that lighter isotope enrichment was observed in the liquid phase, which is the contrary to those of the other systems. Extended X-ray absorption fine structure (EXAFS) analyses were also performed to investigate the coordination structure of the adsorbed or precipitated Ce species that control the isotopic fractionation during adsorption. Even at higher pH, where Ce(CO3 ) + or Ce(CO3 )2 − are the dominant dissolved species, the first coordination sphere of Ce in the solid phase in the Ce/ferrihydrite and Ce/precipitation systems was similar to that observed at pH 5.00 where Ce 3+ was the main species in solution. A slight elongation in the CeO bond length in the solid phase at pH 11.00, where negatively charged dissolved species are dominant in the liquid phase, may cause a decrease in isotopic fractionation in the Ce/δ-MnO2 system. The coordination environment of Ce may not change significantly during the adsorption onto ferrihydrite, because Ce binds to the neutral surface OH group on ferrihydrite at pH below 8.5–8.8 (i.e. the pH of the point of zero charge (PZC) for ferrihydrite), similar to other cations when the metal–O distance was similar in hydrated and adsorbed species. At pH above PZC, Ce bonds to the negatively charged surface OH group, while Ce also bonds with CO3 2− in dissolved species. The reduced partition functions (ln β ) for dissolved species (ln β Lq ) and adsorbed species (ln β So ) with the same trends canceled each other, because ln β of hydrated cation was reduced by the binding anion, resulting in small isotope fractionations. Thus, isotope fractionations for Ce/ferrihydrite may be quite small at the entire pH conditions in this study. The direction of the isotopic fractionation was estimated based on density functional theory (DFT) calculations, which confirmed that lighter Ce is enriched in the liquid phase when Ce forms a complex with carbonate ions. Therefore, this study indicates that the dissolved species can control stable Ce isotopic fractionation during precipitation reactions.